Effect of Pre-Treatments and Additives on the Improvement of Cement Wood Composite A Review - Fatima Zohra Brahmia (BIORESOURCES, 2020)
Cement wood composites (CWC) are a popular construction material. Lightweight or panel-wise wood-based buildings have a growing market in central Europe. Requirements and regulations on both the global and national level are forcing continuous developments. This paper summarizes the research achievements in improving the hygroscopic and mechanical properties and shortening the manufacturing time of CWC via pre-treatments and additives. In addition, new perspectives on enhancing its fire resistance properties by using fire retardant pre-treatments are discussed. CWC without any pre-treatment is a material within the B-s1, dO category of fire resistance. Using fire retardants could upgrade it to the category A(1) but the fire retardants should not affect the primary properties of CWC. There are a number of potential fire retardants of wood that may be used, such as phosphorus, boron, and magnesium compounds.